'Something new and different': student perceptions of content and language integrated learning. (13th March 2021) - Mahan, Karina Rose; Norheim, Helga
Abstract: Content and language integrated learning (CLIL) is a growing field, but we have limited knowledge of how students actually experience CLIL teaching. This study examines why students choose CLIL programmes, how they perceive them, and how they assess their science teaching in English L2. Students from two Norwegian CLIL 11th-grade classes ( N = 50) answered two questionnaires. The results revealed that students primarily chose CLIL programmes because they view English as a key factor to success in their studies and their future work lives. The pros included improving English, classroom environment, and motivation, and the cons were the diminished role of L1, school environment, and cognitive difficulties in learning through L2. Students were satisfied, noting that their teachers clarified the material and often conferred with and challenged them. However, students lacked the freedom to create their own tasks and felt that L1 needed to be more clearly integrated into the teaching.